2014
DOI: 10.1158/1940-6207.capr-13-0378-t
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Endometrial Cancer by n-3 Polyunsaturated Fatty Acids in Preclinical Models

Abstract: Although preclinical and epidemiologic studies have shown the importance of n-3 polyunsaturated fatty acids (PUFA) in the prevention of hormone-responsive cancers such as breast cancer, evidence of the association between n-3 PUFAs and endometrial cancer risk is limited and no previous study has examined the effect of n-3 PUFAs on endometrial cancer in cellular and animal models. In this study, we demonstrated that docosahexenoic acid (DHA) dose-and time-dependently inhibited endometrial cancer cell proliferat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
4
12
0
1
Order By: Relevance
“…The results demonstrated that AA stimulated VCaP cell proliferation (Fig. 1A), which was consistent with previous observations in breast (24) and endometrial (25,26) cancer cell lines. Conversely, EPA effectively inhibited prostate cancer cell growth in vitro.…”
Section: Effect Of ω-3 Pufas On Vcap Cell Growthsupporting
confidence: 92%
“…The results demonstrated that AA stimulated VCaP cell proliferation (Fig. 1A), which was consistent with previous observations in breast (24) and endometrial (25,26) cancer cell lines. Conversely, EPA effectively inhibited prostate cancer cell growth in vitro.…”
Section: Effect Of ω-3 Pufas On Vcap Cell Growthsupporting
confidence: 92%
“…Mammals cannot naturally produce n-3 PUFAs, and so must rely on a dietary supply-from fish, walnuts, olive oil, etc. Since fat-1 transgenic mice carry an abundance of n-3 PUFAs but low levels of n-6 PUFAs in their organs and tissues in the absence of dietary n-3 PUFAs, this resulted in significant benefits with regard to clinical diseases and these mice emerged as a new model for omega-3 research [24], as exemplified as follows: reduced carcinogenesis and cancer prevention [25][26][27] and protection from metabolic diseases [28,29], osteoarthritis [30], several ischemic injuries [31,32], nonalcoholic steatohepatitis [33,34], and oxidative injury [34]. Since Lim et al [35] showed inhibition of hepatocellular carcinoma growth through blocking of bcatenin and COX-2 and these anticancer effects shared the molecular mechanisms of NSAIDs, our group hypothesized that n-3 PUFAs might impose NSAID-sparing effects.…”
Section: Safer Nsaids To Cover the Aforementioned Adverse Effectsmentioning
confidence: 99%
“…Clinically, long-term high intake of diets or supplements enriched in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) were associated with lower risk of endometrial cancer 16 17 . Dietary ω-3 PUFAs significantly attenuated endometrial cancer cell growth in xenograft models 18 . Therefore, high circulating and tissue contents of ω-3 PUFAs may be an important tool in the prevention and treatment of cancer pathogenesis 11 19 .…”
mentioning
confidence: 96%